Investigation of Capacitor Influence in the Impact Factor Index Estimation Due to Voltage Sags and Swells in Distribution Networks - Filiu, David Koller [UNESP]; Cebrian, Juan C. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Currently, electrical utilities must constantly evolve, adapt, and seek ways to achieve power quality goals, and to avoid fines for non-compliance with new standards established by government regulatory bodies. This paper investigates how capacitors affect the power quality index called Impact Factor. This index is used by the Brazilian regulator to quantify the severity of Short Duration Voltage Variation (SDVV), i.e., voltage sags and swell, in users connected to the distribution system. Moreover, this paper proposes the application of a stochastic methodology for the estimation of the Impact-Factor index (IF) for each user taking into account capacitors. The proposed methodology is applied to the IEEE 34-node test feeder network. The results show that the strategic installation of capacitors leads to important reductions in the Impact-Factor index. This investigation allows electrical utilities to identify proper capacitors to improve the quality of services without the need for long measurement periods.
Keywords: Distribution Networks; Impact Factor; Power Quality; Short Duration Voltage Variation